Greenhouse curtain with anti-fog effect
By applying a permanent anti-fog coating composed of water-soluble polymer, inorganic hydrophilic material and crosslinking agent on the polyester film of the greenhouse curtain, the problem of insufficient anti-fog properties in the prior art is solved, and high transparency and long-term UV stability is achieved, supporting plant growth and ensuring long-term use of the greenhouse curtain.
Patent Information
- Application Number
- CN202180082126.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2021-10-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-10-15
AI Technical Summary
The anti-fog properties of the existing greenhouse curtain are not long-lasting, and the transparency and UV stability are insufficient, resulting in reduced photosynthesis and plant decay. The anti-fog coating is easily washed away during the processing step, affecting long-term use.
Using a greenhouse curtain comprising a single or multilayer, high transparency, biaxially oriented, UV-stable polyester film, the polyester film is provided with a permanent anti-fog coating on at least one side, which consists of a water-soluble polymer, an inorganic hydrophilic material and a crosslinker to form a continuous product by knitting, warp knitting or weaving.
Achieve high transparency (at least 92%) and permanent anti-fog properties, with at least 5 years of UV stability, no significant yellowing or embrittlement problems, ensuring support for plant growth and long-term use of greenhouse curtains.
Smart Images

Figure CN116583576B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a greenhouse screen comprising a strip of a single-layer or multi-layer, highly transparent, biaxially oriented, UV-stabilized polyester film provided with a permanent antifog coating on at least one side. The greenhouse screen has a special transparency as well as permanent antifog properties and high UV stability. The invention also relates to a method for producing the polyester film for the greenhouse screen and its use in a greenhouse. Background Art
[0002] Greenhouse shade nets or curtains in greenhouses must meet a series of requirements. They must provide high light transmission in the photosynthetic wavelength range, as this is what plants need for optimal growth. If possible, light transmission should not be affected by weather conditions where condensation forms on the shade curtains.
[0003] Since humidity in greenhouses is usually high, under normal weather conditions (e.g. temperature differences between day and night), condensation forms in the form of water droplets, especially on the surface of the greenhouse shade screen facing the plants. In addition to weather conditions, the different surface tensions of water and plastic also promote condensation formation. In these cases, films with anti-fog properties prevent the formation of water droplets, thereby making the view through the plastic film fog-free.
[0004] Generally speaking, anti-fog additives can be introduced into the polymer matrix during the extrusion process of the film or applied as a coating onto the polymer matrix. Such anti-fog additives are generally divalent compounds that have a non-polar aliphatic region for anchoring in the polymer matrix and a polar hydrophilic portion that can interact with water and reduce the surface tension of water droplets, so that a continuous transparent water film is formed on the film (due to the hydrophilic surface).
[0005] Compared to liquid films, water droplets have a high light scattering and an increased reflective effect, which leads to a significant reduction in photosynthesis, especially in the morning when there is insufficient light. In addition, the decay of plants and plant parts due to non-sticky or dripping water droplets is prevented, and the burning of plants and plant parts due to the droplets acting like burning lenses on the film surface when light falls on them is reduced. If droplets are still formed when condensation is very strong, the anti-fog component must not contain any toxic or particularly harmful substances to the environment. Among the undesirable substances, alkylphenol ethoxylates should be mentioned, which are often used in anti-fog systems (e.g. WO 1995018210). In addition, it is desirable that the greenhouse screen has UV stability, which allows it to be used in the greenhouse for at least 5 years without significant yellowing, brittleness or cracking on the surface and / or a serious reduction in mechanical properties or a significant loss of transparency.
[0006] The use of anti-fog additives in the film should not have a negative impact on light transmission and thus on the transparency of the greenhouse screen to avoid reducing the harvest. Greenhouse screens made of polyester films with various transparent anti-fog coatings are well known. For example, surface active coatings based on hydrophilic water-soluble polymers and / or surfactants are used to coat the surface of the plastic film to achieve an anti-fog effect.
[0007] The basic problem of water-soluble polymers and / or surfactants is that the coating is easily washed off, which means that a permanent anti-fog effect cannot be achieved. Common polyester films with anti-fog coatings are described in EP 1647568 B1 and EP 1777251 B1. These polyester films have good mechanical properties, but exhibit relatively low transparency. In addition, their long-term stability under weathering is relatively low. Moreover, the anti-fog effect of these polyester films has only a short life of several months, because the corresponding anti-fog additives are easily washed off and dissolved in water, so that the active substances will soon be used up when used as greenhouse screens. EP 1152027A1, EP 1534776 A1 and EP 2216362A1 describe polyolefin films based on low-density polyethylene (LDPE), or films based on polyvinyl chloride (PVC) and ethylene-vinyl acetate (EVA), using anti-fog additives based on inorganic hydrophilic colloid substances (colloidal silica, aluminum and others) and non-ionic, anionic or cationic surfactant additives, with lasting anti-fog properties for food packaging and greenhouse applications. These films exhibit permanent anti-fog properties, but their mechanical properties are greatly reduced compared to polyester-based greenhouse screens. For the targeted application, the use of films based on polyolefins can be absolutely ruled out, since polyethylene (PE) degrades more rapidly under UV compared to polyethylene terephthalate (PET) and therefore the required long-term stability and thus a long service life of 5 years cannot be achieved, which has a negative impact on their economic viability. In addition, the low mechanical stability of polyolefins causes the screen to stretch and lose a large part of its closed structure, resulting in a poorer insulating effect.
[0008] EP3456762A2 discloses polyester films with permanent antifog coatings based on porous materials, polymer-based organic crosslinkers, organofunctional silanes and one or more surfactants, suitable for further processing as greenhouse screens. The antifog properties of these films are very good in terms of durability, and the achievable transparency is also within the required range. However, these films show the need to improve the quality of the antifog effect, especially at higher coating thicknesses. In addition, due to regulatory reasons, the use of organofunctional silanes is problematic and undesirable, so this solution must also be excluded.
[0009] Prior art films for greenhouse screens are disadvantageous because their antifog properties are not permanent or the antifog coating is applied to the film in an additional processing step. In addition, prior art polyester films are disadvantageous because they do not have a sufficiently permanent antifog coating in combination with high transparency and long-term stability. Summary of the invention
[0010] It is an object of the present invention to overcome or ameliorate at least some of the disadvantages of prior art screens or to provide a useful alternative. The above objects are achieved by a greenhouse screen and a method of producing a film for said greenhouse screen according to claim 1. Further embodiments are listed in the dependent claims, the description and the drawings.
[0011] As described herein, a greenhouse screen comprising a polyester film is provided, which exhibits a combination of permanent anti-fog properties with a high transparency of at least 92%, UV stability of at least 5 years without significant yellowing, and does not show any embrittlement or cracking of the surface or degradation of mechanical and optical properties that are critical to the application. The film for the greenhouse screen is also economically producible in a thickness range of 10 μm to 40 μm on existing single-layer or multi-layer polyester film production lines.
[0012] This object is solved by providing a greenhouse screen comprising strips of film material which are interconnected by a system of longitudinal and transverse yarns via a knitting, warp knitting or weaving process to form a continuous product. At least 50% of the strips consist of a single-layer or multi-layer coated polyester film having a transparency of at least 92%. The polyester film has a first surface and a second surface, and a permanent anti-fog coating has been applied to at least one surface of the polyester film. The anti-fog coating comprises:
[0013] a) at least one water-soluble polymer;
[0014] b) an inorganic hydrophilic material; and
[0015] c) a cross-linking agent,
[0016] The water-soluble polymer is a polyvinyl alcohol copolymer or a hydrophilic amorphous copolymer.
[0017] Advantageously, the inorganic hydrophilic material is fumed silica, colloidal silica or alumina; advantageously, the crosslinking agent is an oxazoline-modified polymer or other crosslinking agents.
[0018] The polyester film comprises a base layer (B) and optionally a first covering layer (A), or a first covering layer (A) and a second covering layer (C). If present, the first covering layer (A) is applied to the first surface or the second surface of the base layer (B), and if present, the second covering layer (C) is applied to the surface of the base layer (B) opposite to the first covering layer (A).
[0019] A layer in the sense of the present invention is a polymer layer formed by coextrusion. That is, the polyester film according to the invention is formed from one or more layers.
[0020] A coating in the sense of the present invention is a dried product of an aqueous dispersion which is applied to the polyester film and is not part of the extrusion process of the polyester film itself. The coating is applied to the surface of a monolayer or multilayer film.
[0021] Advantageously, the biaxially oriented polyester film (excluding the coating) has a thickness of from 10 μm to 40 μm, preferably from 14 μm to 23 μm, most preferably from 14.5 μm to 20 μm.
[0022] Advantageously, the base layer (B) is at least 70% by weight of a thermoplastic polyester, wherein the thermoplastic polyester consists of at least 90 mol%, preferably at least 95 mol%, of units derived from ethylene glycol and terephthalic acid or from ethylene glycol and naphthalene-2,6-dicarboxylic acid.
[0023] Advantageously, the polyester film contains particles to achieve a certain surface roughness and to improve the winding properties of the film. The particles are selected from calcium carbonate, amorphous silicon dioxide, talc, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, lithium phosphate, calcium phosphate, magnesium phosphate, aluminum oxide, lithium fluoride, calcium, barium, zinc or manganese salts of the dicarboxylic acids used, titanium dioxide, kaolin or particulate polymers such as crosslinked polystyrene or acrylate particles. Amorphous silicon dioxide is preferably used as particles. Preferably, the particles are used in a concentration of less than 0.5% by weight, based on the total weight of the film. Preferably, the particles are present in the covering layer (A) and / or the covering layer (C), but if the film has a multilayer structure, the particles may be present in all layers.
[0024] Advantageously, the base layer (B), and, if present, the cover layers (A) and (C) comprise UV stabilizers.
[0025] The UV stabilizer is selected from the group consisting of triazines, benzotriazoles and benzoxazinones, with triazines being preferred. The base layer (B), and, if present, the cover layers (A) and (C) comprise UV stabilizers in an amount of 0.3% to 3% by weight, preferably 0.75% to 2.8% by weight, based on the total weight of the individual layers.
[0026] The antifog coating has a lower refractive index than the polyester film and a thickness of at least 60 nm and at most 150 nm, preferably at least 70 nm and at most 130 nm, particularly preferably at least 80 nm and at most 120 nm.
[0027] An advantage of the present invention is that the antifog coating according to the present invention does not contain organofunctional silanes which promote adhesion. Organofunctional silanes which promote adhesion are, for example, vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane or γ-glycidoxypropyltrimethoxysilane. These silanes are suspected of being carcinogenic and should therefore be avoided.
[0028] The anti-fog coating is applied to the first or second surface of the polyester film, advantageously the surface of the polyester film opposite the anti-fog coating has an anti-reflection modification, the anti-reflection modification:
[0029] a) is an anti-reflective coating, or
[0030] b) is the top layer modification.
[0031] The top modification is formed by coextrusion on the base layer (B), the top modification comprising a polyester having a lower refractive index than the polyester of the base layer (B). When applied to the surface opposite the antireflective modification, the antifog coating has a thickness of at least 30 nm, preferably at least 40 nm, particularly preferably at least 50 nm and at most 150 nm.
[0032] The coated polyester film for greenhouse screens is produced by extrusion and biaxial stretching, and by:
[0033] a) applying the anti-fog coating composition in-line wet onto a polyester film, followed by heat setting and winding the coated polyester film, or
[0034] b) The polyester film is heat set and wound onto a take-off roll, after which the anti-fog coating composition is applied to the polyester film off-line by conventional coating techniques, followed by drying and winding the polyester film. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] An example arrangement of a greenhouse screen will be described below with reference to the accompanying drawings.
[0036] Figure 1 A portion of a warp knitted veil according to one embodiment is shown on an enlarged scale.
[0037] Figure 2 Portions of a warp knitted curtain according to further embodiments are shown.
[0038] Figure 3 Portions of a woven veil are shown on an enlarged scale.
[0039] Figure 4 Portions of woven veils according to other embodiments are shown. DETAILED DESCRIPTION
[0040] The invention discloses a greenhouse screen comprising strips 11 of membrane material which are connected to each other by a yarn system of longitudinal threads 12, 14, 18 and transverse threads 13a, 13b; 15; 19 via a knitting, warp knitting or weaving method to form Figures 1 to 4 The continuous product disclosed in . The curtain comprises a plurality of narrow strips 11, 11' of membrane material fixed together by yarn frames 12, 13a, 13b; 14, 15; 18, 19. Preferably, the strips 11, 11' of membrane material are closely arranged edge to edge so that they form a substantially continuous surface. The curtain has a longitudinal direction y and a transverse direction x, wherein the strips 11 of membrane material extend in the longitudinal direction. In some embodiments, the strips 11' of membrane material may also extend in the transverse direction. A typical width of the strip is from about 2 mm to about 10 mm.
[0041] exist Figure 1 In the present invention, the strips 11 of membrane material are connected to each other by the warp knitting process described in EP 0 109 951. The yarn frame comprises warp threads 12, which form loops or stitches and extend mainly in the longitudinal direction y. The warp threads 12 are connected to each other by weft threads 13a and 13b extending through the membrane strip.
[0042] Figure 1 An example of a web pattern of a fabric produced by a warp knitting method is shown, wherein four guides are used, one for the strip 11 of membrane material, two for the connecting weft threads 13a and 13b extending transversely to the membrane strip, and one for the longitudinal warp threads 12.
[0043] In the figure, the spaces between the strips 11 of membrane material have been greatly exaggerated to make the mesh pattern clear. Typically, the strips 11 of membrane material are closely positioned edge to edge. The longitudinal warp threads 12 are arranged on one side of the curtain, i.e. the lower side, while the transverse connecting weft threads 13a and 13b are located on both sides of the fabric, i.e. the upper side and the lower side. The term "transverse" in this regard is not limited to a direction perpendicular to the longitudinal direction, but means that the connecting weft threads 13a and 13b extend through the strips 11 of membrane material, as shown in the figure. Preferably, the connection between the longitudinal warp threads 12 and the transverse weft threads 13a and 13b is made on the lower side of the fabric. The strips 11 of membrane material can be closely arranged edge to edge in this way without being restricted by the longitudinal warp threads 12.
[0044] In a series of knitted stitches, the so-called open pillar stitch formation, Figure 1 The longitudinal warp threads 12 in the web extend continuously in an uninterrupted manner along the opposite edges of adjacent strips 11 of film material.
[0045] The transverse weft threads 13a and 13b pass over and under the strip 11 of membrane material at the same position (ie opposite to each other) to securely capture the strip of membrane material. Each knit stitch in the longitudinal warp threads 12 has two of these transverse weft threads 13a and 13b engaged therewith.
[0046] Figure 2 Shown with Figure 1 A further example of a mesh pattern of a similar fabric is shown. The difference is that the transverse weft threads 13a and 13b pass through one and two strips 11 of membrane material in an alternating manner.
[0047] Figure 3 A woven curtain is shown in which strips 11 of membrane material are interconnected by warp threads 14 extending in the longitudinal direction y and interwoven with weft threads 15 extending mainly in the transverse direction x through the strips 11 of membrane material.
[0048] Figure 4 A further embodiment of the woven curtain described in US 5,288,545 is shown, comprising strips 11 (warp strips) of membrane material extending in the longitudinal direction y and strips 11 ' (weft strips) of membrane material extending in the transverse direction x. Figure 4 As shown, the weft tapes 11' in the transverse direction may always be on the same side of the warp tapes 11 in the longitudinal direction, or may alternately be above and below the longitudinal warp tapes 11. The warp tapes 11 and weft tapes 11' are fixed together by a yarn frame comprising longitudinal threads 18 and transverse threads 19. The curtain may contain open areas without tapes to reduce heat accumulation under the curtain.
[0049] The films used in the greenhouse screens described herein are very suitable as highly transparent convection grids. Here, the films are usually cut into narrow strips with a width of 2 to 10 mm and then produced together with polyester yarns (which must also be UV-stabilized) to produce fabrics or screens for use as coverings in greenhouses. Greenhouse screens can contain strips of the films described herein in combination with strips of other films, in particular films with a light-scattering effect or films that promote a further increase in transparency. It is also possible to make screens with "open" areas without strips, allowing ventilation through the screen.
[0050] In order to provide the desired light transmission properties, at least 50%, preferably at least 60%, more preferably at least 70%, more preferably at least 80%, more preferably at least 90% of the strips in the curtain should be strips 11 coated with a single layer or a multilayer film as described herein. According to one embodiment, all the strips 11 in the curtain have the single layer or multilayer polyester film as described, and the strips 11 are closely arranged edge to edge to form a substantially continuous surface. Optionally, the film itself can also be installed in the greenhouse.
[0051] membrane
[0052] The strip of film material used to make the above greenhouse screen comprises a single-layer or multi-layer polyester film having a transparency of at least 92%, wherein the polyester film has a first surface and a second surface, wherein a permanent anti-fog coating is applied to at least one of the first surface or the second surface of the polyester film.
[0053] The polyester film described herein comprises at least a base layer (B), which preferably contains at least 70% by weight of a thermoplastic polyester. Suitable for this are polyesters of ethylene glycol and terephthalic acid (=polyethylene terephthalate, PET), polyesters of ethylene glycol and naphthalene-2,6-dicarboxylic acid (=polyethylene-2,6-naphthalate, PEN), polyesters of 1,4-bishydroxymethylcyclohexane and terephthalic acid [=poly(1,4-cyclohexenedimethylene terephthalate), PCDT], and polyesters from ethylene glycol, naphthalene-2,6-dicarboxylic acid and biphenyl-4,4'-dicarboxylic acid (=polyethylene-2,6-naphthalate biphenyl, PENBB). Particularly preferred are polyesters composed of at least 90 mol %, preferably at least 95 mol %, of ethylene glycol and terephthalic acid units or ethylene glycol and naphthalene-2,6'-dicarboxylic acid units. In a particularly preferred version of the polyester film, the base layer (B) is made of a polyethylene terephthalate homopolymer.
[0054] The film material may comprise one or more additional layers (intermediate layers or cover layers), as further explained below. Preferably, the cover layer is also made of a polyester as described above, with the same or different composition as the base layer described above.
[0055] The production of polyesters can be accomplished, for example, by the transesterification process. This process starts with a dicarboxylic acid ester and a diol, reacting with a conventional transesterification catalyst, such as a zinc salt, a calcium salt, a lithium salt, a magnesium salt, and a manganese salt. The intermediate product is then condensed in the presence of a conventional polycondensation catalyst, such as antimony trioxide or a titanium salt. They can also be produced by a direct esterification process in the presence of a polycondensation catalyst. This process starts directly with a dicarboxylic acid and a diol.
[0056] Suitable aromatic dicarboxylic acids are benzene dicarboxylic acids, naphthalene dicarboxylic acids (for example naphthalene-1,4-dicarboxylic acid or naphthalene-1,6-dicarboxylic acid), biphenyl-x,x'-dicarboxylic acids (especially biphenyl-4,4'-dicarboxylic acid), diphenyl acetylene-x,x'-dicarboxylic acids (especially diphenyl acetylene-4,4'-dicarboxylic acid) or stilbene-x,x'-dicarboxylic acids. Among the cycloaliphatic dicarboxylic acids, cyclohexane dicarboxylic acids (especially cyclohexane-1,4-dicarboxylic acid) are advantageous. Among the aliphatic dicarboxylic acids, (C3-C 19 )Alkanedioic acids are particularly suitable, the alkyl component of which may be straight-chain or branched. Among the heterocyclic dicarboxylic acids, 2,5-furandicarboxylic acid is advantageous.
[0057] Aliphatic diols suitable for the process are, for example, diethylene glycol, triethylene glycol, aliphatic diols of the general formula HO-(CH2)n-OH, where n represents an integer from 3 to 6 (in particular propane-1,3-diol, butane-1,4-diol, pentane-1,5-diol and hexane-1,6-diol) or branched aliphatic diols having up to 6 carbon atoms. Cycloaliphatic diols include cyclohexanediol (in particular cyclohexane-1,4-diol). Suitable other aromatic diols correspond, for example, to the formula HO-C6H4-X-C6H4-OH, where X represents -CH2-, -C(CH3)2-, -C(CF3)2-, -O-, -S- or -SO2-. Bisphenols of the formula HO-C6H4-C6H4-OH are also very suitable.
[0058] Advantageously, the polyester film contains particles in order to achieve a certain surface roughness and to improve the winding of the film.
[0059] Useful particles are, for example, calcium carbonate, amorphous silicon dioxide, talc, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, lithium phosphate, calcium phosphate, magnesium phosphate, aluminum oxide, lithium fluoride, calcium, barium, zinc or manganese salts of the dicarboxylic acids used, titanium dioxide, kaolin or particulate polymers such as crosslinked polystyrene or acrylate particles. Amorphous silicon dioxide is preferably used as a particle. Preferably, the particles are used in a concentration of less than 0.5% by weight, based on the total weight of the film. Preferably, no other particles that influence the surface properties and rheological properties of the film are present in the film.
[0060] If the film has a multilayer structure, the particles may be present in all layers, preferably in the cover layer.
[0061] The film must also have a low transmittance in the wavelength range from below 370 nm to 300 nm. For each wavelength in this specified range, the UV light transmittance is below 40%, preferably below 30%, particularly preferably below 15% (for the measurement procedure, see measurement methods). This protects the film material of the curtain from embrittlement and yellowing, and also protects the plants and installations in the greenhouse from UV light. At 390 nm to 400 nm, the transparency is greater than 20%, preferably greater than 30%, particularly preferably greater than 40%, because this wavelength range is already significantly photosynthetically active, and if the filter is too strong in this wavelength range, plant growth will be negatively affected.
[0062] Low UV light transmission is achieved by adding organic UV stabilizers. Low transmission of UV light also protects the flame stabilizer (which may also be present) from rapid destruction and severe yellowing. The organic UV stabilizer is selected from the group consisting of triazines, benzotriazoles or benzoxazinones. Triazines are particularly preferred because they exhibit good thermal stability and low film outgassing at the processing temperatures of 275° C. to 310° C. typical for PET. Particularly suitable is 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(hexyl)oxyphenol (e.g. 1577, BASF) or 2-(2'-hydroxyphenyl)-4,6-bis(4-phenylphenylphenyl)triazine (e.g. Tinuvin TM 1600, BASF). If these UV stabilizers are used, preferably low transparency values below 370 nm can already be achieved at lower stabilizer concentrations, while higher transparency values are achieved at wavelengths above 390 nm.
[0063] Film, or in the case of a multilayer film, all film layers contain at least one organic UV stabilizer. The UV stabilizer is added to the cover layer or the monofilm in a preferred form in an amount of 0.3% to 3% by weight based on the weight of each layer. A UV stabilizer content of 0.75% to 2.8% by weight is particularly preferred. Ideally, the cover layer should contain 1.2% to 2.5% by weight of UV stabilizer. Preferably, in the multilayer version of the film, the base layer and the cover layer contain UV stabilizers, wherein the UV stabilizer content (weight %) in the base layer is preferably lower than the content in the cover layer. These contents in the cover layer refer to the content of triazine derivatives. If a UV stabilizer from a benzotriazole or benzoxazinone is used in whole or in part to replace the triazine derivative, the replacement part of the triazine component must be replaced by 1.5 times the amount of the benzotriazole or benzoxazinone component.
[0064] The film may contain other stabilizers, such as phosphorus compounds, such as phosphoric acid and its derivatives, such as phosphate esters, or phosphonic acid and their derivatives, such as phosphonate esters, to provide the film with reduced flammability.
[0065] The total thickness of the polyester film according to the invention can vary within certain limits. It is from 10 μm to 40 μm, preferably from 14 μm to 23 μm, particularly preferably from 14.5 μm to 20 μm, wherein the base layer (B) preferably accounts for 60% to 90% of the total thickness in the multilayer variant. Preferably, the proportion of the base layer (B) in the three-layer version is at least 60%, particularly preferably at least 70%, very particularly preferably at least 75% of the total film thickness.
[0066] In addition to self-renewable materials, polyester raw materials that have undergone a recycling process can also be used. Since recycled polyester raw materials can come from various sources with different raw material qualities, it is important to allow only sources that can guarantee a certain degree of purity. In this case, it is shown that so-called PCR materials (post-consumer recycled materials) (referring to raw materials recovered from old products that have already been used by customers) can surprisingly be used well for the production of films and are also suitable as the basis for the films disclosed herein. The transparency of the film then decreases slightly, while the turbidity may increase slightly due to the lower content of possible impurities. Surprisingly, the loss of transparency (which is crucial for the performance of the greenhouse screen, as described below) is smaller than expected, which is probably due to the leveling side effect of the permanent anti-fog coating.
[0067] The film may have a three-layer structure, wherein the first covering layer (A) is on one side of the base layer (B) and the second covering layer (C) is on the opposite side of the base layer (B). In this case, the two covering layers (A) and (C) form the first covering layer (A) and the second covering layer (C). In some embodiments, the first covering layer (A) and the second covering layer (C) may be the same. The polyester film may also have a two-layer structure, wherein the base layer (B) is provided with only the first covering layer (A).
[0068] The anti-fog coating can be applied to the first covering layer (A) and / or the second covering layer (C). A three-layer structure can be used to obtain a film with good transparency, wherein the base layer (B) does not contain particles other than particles introduced by its own self-renewable materials. In this way, the proportion of recycled regrind can be increased, making the film production particularly economical. Self-renewable materials are the terms used to describe film residues / waste (e.g., side strips) generated during the film production process. These can be directly recycled during the production process or first collected and then added during the production process of the base layer (B).
[0069] Without impairing the properties of the film, the proportion of recycled polyester material returned should be as high as possible. In the films disclosed herein, the proportion of recycled polyester material in the base layer (B) can be 0% to 60% by weight, preferably 0% to 50% by weight, particularly preferably 0% to 40% by weight, based on the total weight of the film.
[0070] Greenhouse screens comprising the films disclosed herein have a transparency of at least 92%, preferably 93%, particularly preferably 94%, ideally at least 94.5%. The higher the transparency, the better the support for plant growth in the greenhouse.
[0071] The transparency of the present invention is achieved by a permanent anti-fog coating on at least one surface of the polyester film.
[0072] Anti-fog coating and anti-reflective modification
[0073] In one version, the polyester film has an antifog coating applied to one surface. Minimum transparency values can be achieved by this design. The antifog coating described below must have a lower refractive index than the polyester film. In the longitudinal direction of the film, the refractive index of the antifog coating at a wavelength of 589nm is lower than 1.64, preferably lower than 1.60, and ideally lower than 1.58. In addition, the dry film thickness of the antifog coating must be at least 60nm, preferably at least 70nm, particularly at least 80nm, and a maximum of 150nm, preferably a maximum of 130nm, and ideally a maximum of 120nm. This achieves an ideal increase in transparency within the desired wavelength range. Below 60nm thickness, the antifog coating no longer has enough contribution to the increase in transparency. If the dry coating thickness of a maximum of 150nm is exceeded, additional applications will not further increase transparency. In addition, higher coating consumption reduces the economic benefits of the film.
[0074] In another embodiment, the anti-fog coating has a dry film thickness of at least 30 nm, preferably at least 40 nm, particularly preferably at least 50 nm and at most 60 nm. This achieves a permanent anti-fog effect in accordance with the present invention. However, in order to achieve the transparency value of at least 92% required by the present invention, in this embodiment, the polyester film must be provided with an anti-reflection modification on the film side opposite to the anti-fog coating. The anti-reflection modification can be formed by an anti-reflection coating or a top layer modification, both of which must have a lower refractive index than polyethylene terephthalate. If the anti-reflection modification is formed by an anti-reflection coating, this coating must have a lower refractive index than the polyester film. In the machine direction of the film, the refractive index of the anti-reflection coating at a wavelength of 589 nm is below 1.64, preferably below 1.60, and ideally below 1.58. The anti-reflection coating can be applied to any surface of the polyester film opposite to the anti-fog coating, i.e., on the surface of the base layer (B) in the case of a single-layer film or a double-layer film, or on any top surface of the top layer (A) or (C) in the case of a multilayer film.
[0075] Polyacrylates, silicones and polyurethanes as well as polyvinyl acetate are particularly suitable. Suitable acrylates are described, for example, in EP-A-0 144 948 and suitable silicones are described, for example, in EP-A-0 769 540. Coatings based on polyacrylates and polyurethanes are particularly preferred because they are less susceptible to leaching of coating components or flaking in greenhouses, as is more likely with silicone-based coatings.
[0076] Preferably, the antireflective coating contains less than 10% by weight, more preferably less than 5% by weight, and most preferably less than 1% by weight of repeating units containing aromatic structural elements. When the repeating units containing aromatic structural elements are above 10% by weight, the weathering stability of the coating deteriorates significantly. The antireflective coating contains at least 1% by weight (dry weight) of UV stabilizers, preferably Tinuvin 479 or Tinuvin 5333-DW. Less preferred are HALS (hindered amine light stabilizers) because these cause a significant yellowing of the material during the regeneration process (recycling of film residues from production), resulting in reduced transparency.
[0077] The thickness of the anti-reflection coating is at least 60nm, preferably at least 70nm, particularly at least 80nm, and a maximum of 130nm, preferably a maximum of 115nm, and ideally a maximum of 110nm. This achieves an ideal increase in transparency within the desired wavelength range. In a preferred design, the thickness of the coating is greater than 87nm, particularly preferably greater than 95nm. In this preferred design, the thickness of the anti-reflection coating is preferably less than 115nm, ideally less than 110nm. In this narrow thickness range, the increase in transparency is close to the optimal state, and at the same time, compared with other parts of the visible spectrum, the reflection of the light of the UV and blue ranges in this thickness range increases. This saves UV stabilizers on the one hand, but the most important thing is to cause a shift in the blue / red ratio, which is beneficial to the red component. This makes plant growth improve and flowering and fruiting increase. Suitable anti-reflection coatings are described in Examples 1 to 3 of EP3251841B1.
[0078] If the antireflection modification is formed by a top modification, the top modification is formed by coextrusion on the base layer (B) and is located on the film side opposite the antifog coating. It should be noted that the top modification is never coextruded on the cover layer (A) or (C). This top modification must consist of a polyester with a lower refractive index than the polyester of the base layer (B). In the machine direction of the top layer applied by coextrusion, the refractive index at a wavelength of 589 nm is below 1.70, preferably below 1.65, particularly preferably below 1.60. This refractive index is achieved by a polymer containing a comonomer content of at least 2 mol%, preferably at least 3 mol%, ideally at least 6 mol%. If the comonomer content is below 2 mol%, these refractive index values cannot be achieved. The comonomer content is below 20 mol%, particularly preferably below 18 mol%, particularly preferably below 16 mol%. Above 16 mol %, the UV stability deteriorates significantly due to the amorphous nature of the layer, while above 20 mol %, even with the addition of UV stabilizers, the same level of UV stability as below 16 mol % cannot be achieved.
[0079] Comonomers are all monomers except ethylene glycol and terephthalic acid (or dimethyl terephthalate). Preferably, no more than two comonomers are used simultaneously. Particularly preferred isophthalic acid as a comonomer. Preferably, the layer with a comonomer content of more than 8 mol % (based on the polyester in the layer, or its dicarboxylic acid component) also contains at least 1.5 wt. %, particularly preferably more than 2.1 wt. %, of organic UV stabilizer, based on the total weight of the layer, to compensate for the poorer UV stability of the layer with an increased comonomer content.
[0080] In another particularly preferred design, both polyester film surfaces are provided with an antifog coating having a thickness of at least 60 nm, preferably at least 70 nm, in particular at least 80 nm and a maximum of 150 nm, preferably a maximum of 130 nm, and ideally a maximum of 120 nm. In the machine direction of the film, the refractive index of the two antifog coatings at a wavelength of 589 nm is below 1.64, preferably below 1.60, and ideally below 1.58. By providing the antifog coating on both surfaces of the polyester film, a preferred transparency value of at least 94.5% can be achieved. Due to the use of a single coating composition, a highly transparent film with very good permanent antifog properties (cold fog and hot fog test) can be produced particularly economically in this way. Such a film is particularly suitable for use in greenhouses with continuous high humidity (condensation), because the double-sided antifog coating prevents the formation of water droplets on both sides of the film surface and effectively prevents the resulting light scattering.
[0081] In order to achieve a permanent anti-fog effect in accordance with the present invention, the film must be provided with a permanent anti-fog coating on at least one side. If the formation of fine water droplets (e.g. condensation in a greenhouse) is not observed on the surface of the polyester film and the wash-off resistance of the coating is good, the permanent anti-fog properties of the surface are achieved. The minimum requirement for good anti-fog properties is a high surface energy or a low contact angle α (see the method section). If the surface tension of the anti-fog surface is at least 45 mN / m, preferably at least 55 mN / m, and particularly preferably at least 60 mN / m, the anti-fog properties are good enough. A permanent anti-fog effect of at least one year can be achieved in a cold fog test, and a permanent anti-fog effect of at least three months can be achieved in a hot fog test (required grades A and B; see the method section or the example table). Permanent anti-fog properties and a transparency of at least 92% are achieved by using the coating composition described below.
[0082] The anti-fog coating is formed by drying the anti-fog coating composition described herein. In the case of a multi-layer design with an anti-reflective modified coextruded layer, a permanent anti-fog coating is applied to the side of the film opposite the anti-reflective modified coextruded layer.
[0083] The anti-fog coating composition according to the present invention (also referred to herein as coating solution and coating dispersion) is an aqueous solution comprising a) polyvinyl alcohol (PVOH) or a hydrophilic PVOH copolymer, b) an inorganic hydrophilic material, and c) a crosslinking agent.
[0084] Common anti-fog coatings contain surfactants to achieve permanent anti-fog properties. However, the use of surfactants is disadvantageous, especially in the case of online production. Surprisingly, it has been found that the use of polyvinyl alcohol or hydrophilic amorphous copolymers in anti-fog coatings produces good permanent anti-fog properties, and the use of surfactants can be omitted in such anti-fog coatings.
[0085] Component a) is a polyvinyl alcohol copolymer or a hydrophilic amorphous copolymer.
[0086] When using polyvinyl alcohol copolymers, it is advantageous to have a medium to high saponification degree of 60% to 95%, preferably 70% to 90%, such as Gohsenol KP08R (saponification degree 71% to 73.5%), to ensure solubility in water without causing the raw material to be washed away too quickly. Low-saponification copolymers are also possible if groups that simplify solubility in water are included instead of acetate groups. In this case, part of the acetate groups in the polyvinyl alcohol are replaced by polyethylene glycol. An example of such a polyvinyl alcohol copolymer is Gohsen X-LW200, which is highly water-soluble despite its saponification degree of only 46% to 53%.
[0087] The polyvinyl alcohol copolymer according to the present invention is an alkanediol-polyvinyl alcohol copolymer. Preferably, the alkanediol-polyvinyl alcohol copolymer is selected from propylene glycol-polyvinyl alcohol copolymer, butanediol-polyvinyl alcohol copolymer, pentanediol-polyvinyl alcohol copolymer or a mixture thereof. The polyvinyl alcohol copolymer butanediol-polyvinyl alcohol copolymer is particularly preferred.
[0088] Particularly preferred polyvinyl alcohol copolymers of this type are sold under the trade name Nichigo G-Polymer, which stands for butanediol-vinyl alcohol copolymer, which is highly water-soluble at a saponification degree of 86% to 99%, exhibits a low foaming tendency in aqueous media, and is well wetted by water droplets as a coating part on PET (e.g. G-Polymer OKS8089).
[0089] In general, polyethylene glycols or cellulose ethers are also conceivable, but these substance classes are often difficult to apply to the film in a so-called inline process or have a negative impact on the recyclability / recyclability of the film. Polyethylene glycols have a decomposition temperature in the temperature range of polyester film production, so loss-free production is not possible. If the film is provided with an antifog coating containing cellulose ethers, this results in poor recyclability of the film, since temperatures above 250° C. occurring during the regeneration process lead to decomposition of the cellulose ethers, which results in a clearly perceptible yellow coloration of the resulting recyclates. Recyclates produced in this way can no longer be used to produce films for which the optical properties represent a key qualification.
[0090] Component a) is used in a concentration of 2% to 10% by weight, preferably 4% to 8% by weight, based on the total solids content of the coating solution. It is characterized by good film-forming properties, in particular in in-line processes.
[0091] As component b), inorganic and / or organic particles can be used, such as fumed silica, inorganic alkoxides containing silicon, aluminum or titanium (as described in DE 698 33 711), kaolin, crosslinked polystyrene or acrylate particles. Preferably, porous SiO2 (such as amorphous silica), and pyrogenic metal oxides, or aluminum silicates (zeolites) are used. These materials are used in a concentration of 1% to 6% by weight (relative to the coating dispersion), preferably 2% to 4% by weight (relative to the coating dispersion). In addition, SiO2 nanoparticles can be used additionally or exclusively to further improve the wettability of the film surface and absorb enough water to form a uniform water film, thereby producing an anti-fog effect. Hydrophilic fumed silica, such as Aerodisp W7622 (Evonik Resource Efficiency GmbH), is particularly suitable, which contains 22% by weight of SiO2 particles with an average aggregate size of 0.10 μm.
[0092] Furthermore, the coating dispersion contains component c in a concentration of 2% to 10% by weight (relative to the coating dispersion), preferably 4% to 8% by weight (relative to the coating dispersion). Preferably, the coating dispersion is an oxazoline-modified polymer (oxazoline-based crosslinker), such as is available from Nippon Shokubai under the trade name EPOCROS WS-500, in particular EPOCROS WS-700. By using the above-mentioned amount of crosslinker, the wear resistance of the coating is improved. Other crosslinkers, such as melamine, are compounds containing a large amount of nitrogen atoms and tend to give the film a yellowish appearance when regenerated. Therefore, melamine is not suitable for anti-fog coatings applied to film materials to be used in greenhouse screens.
[0093] Optionally, surfactants can be added to the dispersion to improve the anti-fog effect. However, the cost of doing so is the disadvantage that the permanent anti-fog coating can no longer be well applied to the film in the online method. Assuming that the surfactants are in contrast to the other polymer components of the coating dispersion, they may have evaporated during the film production process and are therefore no longer usable for the intended purpose. In the offline method, this situation can be resisted by preselecting milder drying conditions. However, the disadvantage of the offline method is the additional expenditure in the form of at least one further processing step, so if possible, additional surfactants should be avoided. Possible surfactants that can be further added include polyalkylene glycol ethers, polysorbate 80 (polyoxyethylene (20) sorbitan monooleate), sulfosuccinates, alkyl sulfates / esters, alkylbenzene sulfates / esters. The possible addition amount in the coating dispersion is up to 7% by weight, but preferably <0.2% by weight, ideally 0% by weight.
[0094] In addition, the coating solution may contain one or more defoamers. The use of defoamers has proven to be particularly advantageous for highly concentrated dispersions, since here the foam formation on the coating apparatus can be reduced, thereby ensuring a stable production process. However, it must be accepted that the addition of defoamers, and even the addition of amphoteric or surfactant additives, can potentially lead to coating inhomogeneities on the film surface. Therefore, the use of such additives must be carefully weighed and the dosage should be kept fairly low.
[0095] Above the limits specified by the invention, the economic efficiency of the film is reduced due to the use of excess coating components. Below the limits according to the invention, the desired antifogging properties occur only to a limited extent (not permanently) due to the required coating thickness being too low. By observing the limits of the invention, the reaction product of the coating dispersion, in particular on a biaxially stretched polyester film, provides a good antifogging effect, a high wash-off resistance and a high hydrophilicity.
[0096] Production method
[0097] The method for producing polyester film is described, for example, in the chapter "Polyesters, Films" in "Handbook of Thermoplastic Polyesters, Ed. S. Fakirov, Wiley-VCH, 2002" or "Encyclopedia of Polymer Science and Engineering, Vol. 12, John Wiley & Sons, 1988". A preferred method for producing the film comprises the following steps. Each layer of the raw material is melted in an extruder and extruded through a single-layer or multi-layer slit die onto a cooled take-off roll. The film is then reheated and stretched ("oriented") in the longitudinal (MD or machine direction) direction and the transverse (TD or transverse) direction or in the transverse and longitudinal directions. The film temperature during stretching is usually higher than the glass transition temperature T of the polyester used. g The film is then heat-set at an oven temperature of 180° C. to 240° C., in particular at 210° C. to 230° C. The film is then cooled and rewound.
[0098] Preferably, the biaxially oriented polyester film described herein is coated in-line, i.e. the coating is applied during the film manufacturing process prior to longitudinal stretching and / or transverse stretching. In order to achieve good wetting of the polyester film with the aqueous coating composition, the surface is preferably first corona treated. The anti-fog coating can be applied using common suitable methods such as slot casting or spraying methods. Particularly preferred is the application of the coating by the "reverse gravure roll coating" method, in which 1.0 g / m 2 Up to 3.0g / m 2 The coating is applied very uniformly with an applied weight (wet weight) of 100%. It is also preferred to apply by the Meyer-Rod method, which can achieve greater coating thicknesses. Preferably, the coating on the finished film has a thickness of at least 60 nm, preferably at least 70 nm, particularly preferably at least 80 nm. In this case, an in-line method is economically more attractive, because in the case of coatings on both sides, the antifog coating and the antireflection coating can be applied simultaneously, so that one method step can be saved (see below: off-line method).
[0099] In an alternative method, the above-mentioned coating is applied by an off-line technique. In the off-line application method, in an additional processing step after the film production, an anti-reflective coating and / or an anti-fog coating are applied to the corresponding surface of the polyester film by an off-line technique using an engraved roller (positive gravure). The maximum limit is determined by the process conditions and the viscosity of the coating dispersion, and its upper limit is found in the processability of the coating dispersion. The anti-fog coating and the anti-reflective coating can be applied to the surface of a multilayer film (i.e. a film containing a base layer (B) and two covering layers (A) and (C)), to the surface of a two-layer film (i.e. a film containing a base layer (B) and one covering layer (A)), or to a monolayer film (i.e. a film containing only a base layer (B)). Although it is in principle possible to apply both an anti-fog coating and an anti-reflective coating on the same surface side of a polyester film, it has been proven that applying an anti-fog coating to a base coating (anti-fog coating applied to an anti-reflective coating) is disadvantageous because on the one hand the material consumption increases and on the other hand an additional processing step is required, which reduces the economic efficiency of the film.
[0100] With some in-line coating methods, particularly preferred coating thicknesses cannot be achieved due to the high viscosity of the coating dispersion. In this case, it is advisable to select an offline coating method, since dispersions with lower solids contents and higher wet applications can be processed here, making processing easier. In addition, higher coating thicknesses can be achieved using offline coating, which has proven to be advantageous for applications where high demands are made on the longevity of the antifog effect. For example, coating thicknesses of ≥ 80 nm can be achieved particularly easily with offline methods, which enables a better permanent antifog effect to be achieved, but the transparency is not further improved.
[0101] Test method description
[0102] The following measurements were used to characterize the materials and films within the scope of the present invention:
[0103] UV / Vis spectrum, transmittance at wavelength x
[0104] The transmittance of the film at different wavelengths was measured in a UV / Vis double beam spectrometer (Lambda 950S) from Perkin Elmer, USA. A film sample with a measuring size of approximately 3×5 cm was inserted into the beam path perpendicular to the measuring beam through a flat sample holder. The measuring beam passed through an integrating sphere to a detector, where the intensity was measured to determine the transparency at the desired wavelength. The background was air. The transmittance was read at the desired wavelength.
[0105] Haze, transparency
[0106] This test is used to determine the haze and clarity of plastic films where optical clarity or haze is critical to practical value. Measurements are made on a Hazegard Hazemeter XL-21 1 from BYK Gardner according to ASTM D 1003-61.
[0107] Determination of the refractive index as a function of wavelength
[0108] To determine the variation of the refractive index of the film substrate and the applied coating as a function of wavelength, spectroscopic ellipsometry was used.
[0109] The analysis was conducted based on the following references:
[0110] JAWoollam et al.: Overview of variable-angle spectroscopic ellipsometry (VASE): I. Basic theory and typical applications. In: Optical Metrology, Proc. SPIE, Volume 72 (Ghanim AA-J., Ed.); SPIE-The International Society of Optical Engineering, Bellingham, WA, USA (1999), pp. 3-28.
[0111] First, the base film of the coextruded side without coating or modification was analyzed. In order to suppress the back reflection, the back of the foil was roughened with sandpaper with a particle size as small as possible (e.g. P1000). The film was then measured with a spectroscopic ellipsometer equipped with a rotating compensator (here M-2000 from JA Woollam Co, Inc, Lincoln, NE, USA). The longitudinal direction of the sample was parallel to the light beam. The wavelengths measured were 370 nm to 1000 nm and the measuring angles were 65°, 70° and 75°.
[0112] The model is then used to simulate the ellipsometric data Ψ and Δ.
[0113] In this case, the Cauchy model (wavelength λ, unit is μm) is suitable.
[0114] Vary the parameters A, B and C so that the data corresponds as closely as possible to the measured spectra Ψ (amplitude ratio) and Δ (λ). To check the quality of the model, include the mean square error (MSE) value, which should be as small as possible, and compare the model with the measured data (Ψ(λ) and Δ(λ)).
[0115]
[0116] a = number of wavelengths, m = number of fitting parameters, N = cos(2Ψ), C = sin(2Ψ)cos(Δ), S = sin(2Ψ)sin(Δ)
[0117] The Cauchy parameters A, B and C obtained for the base film allow the calculation of the refractive index n as a function of wavelength and are valid in the measurement range of 370 nm to 1000 nm.
[0118] Coatings or modified coextruded layers can be analyzed in a similar way. To determine the refractive index of the coating and / or coextruded layer, the back of the film must also be roughened as described above. Here, too, the Cauchy model can be used to describe the refractive index as a function of wavelength. However, the layers are now located on a known substrate. Since the parameters of the base film are now known, they should remain constant during the modeling process, which is taken into account in the respective evaluation software (CompleteEASE or WVase). The layer thickness influences the obtained spectrum and must be taken into account during the modeling.
[0119] Surface free energy
[0120] The surface free energy was determined according to DIN 55660-1.2. Water, 1,5-pentanediol and diiodomethane were used as test liquids. The static contact angle between the surface of the coated film and the tangent to the surface profile of a horizontally placed droplet was determined using the measuring device DSA-100 from Krüss GmbH, Hamburg, Germany. The discharge film samples were measured at 23°C ± 1°C and 50% relative humidity, and the discharge film samples had previously been conditioned in a standard climate for at least 16 hours. The surface free energy σs (total) was evaluated according to the Owens-Wendt-Rabel-Kaelble (OWRK) method by the software Advance Ver.4 belonging to the device. The surface tension parameters of the three standard liquids are as follows, see Table 1:
[0121] Table 1: Surface tension parameters of three standard liquids
[0122]
[0123] Determination of anti-fog effect
[0124] Cold fog test: The anti-fogging properties of polyester films were determined as follows: The film samples were sealed on a menu tray (about 17 cm long, about 12 cm wide, about 3 cm high) made of amorphous polyethylene terephthalate (=APET) containing about 50 mL of water in a laboratory at a temperature of 23°C and a relative humidity of 50%. The tray was stored in a refrigerator at a temperature of 4°C, placed at an angle of 30° and taken out for evaluation after 12 h, 24 h, 1 week, 1 month and 1 year. When the warm air at 23°C was cooled to refrigerator temperature, the formation of condensation was checked. Films provided with an effective anti-fogging agent are transparent even after the formation of condensation, because the condensate forms a coherent transparent film. In the absence of an effective anti-fogging agent, fine fog droplets are formed on the film surface resulting in a reduction in the transparency of the film; in the worst case, the contents of the menu tray are no longer visible.
[0125] Another test method is the so-called hot steam or hot fog test. The QCT condensation tester from Q-Lab is used for this. This simulates the anti-fogging effect of the climate humidity by condensing warm water directly on the film. In a few days or weeks, the results caused by moisture over months or years can be reproduced. For this purpose, the water is tempered to 60°C in the QCT condensation device and the film is clamped on the corresponding holder. The coated film has an inclination angle of about 30°. The evaluation method is the same as above. With this test, the long-term anti-fogging effect or wash-off resistance of the film can be tested, because steam constantly condenses on the film and flows away and / or drips again. As a result, easily soluble substances are washed off and the anti-fogging effect is weakened. This test is also carried out in the laboratory at a temperature of 23°C and a relative humidity of 50%.
[0126] The anti-fog effect was assessed visually (anti-fog test).
[0127] Rating:
[0128] A transparent film that shows no visible water, i.e. completely transparent: excellent anti-fog effect.
[0129] There are some random, irregularly distributed water droplets on the surface B, and a discontinuous water film: acceptable anti-fog effect.
[0130] C Complete layer of large transparent water droplets, poor visibility, lens formation, water droplet formation: poor anti-fog effect.
[0131] D Opaque or transparent layer of large water droplets, no transparency, poor light transmittance: the anti-fog effect is very poor.
[0132] Standard viscosity (SV-value)
[0133] The standard viscosity of the diluted solution SV is measured in an Ubbelohde viscometer at (25 ± 0.05) ° C in accordance with DIN 53 728 Part 3. Dichloroacetic acid (DCE) is used as solvent. The concentration of the dissolved polymer is 1 g polymer / 100 mL pure solvent. The polymer is dissolved at 60 ° C for 1 hour. If the sample is not completely dissolved after this time, a dissolution test is carried out at 80 ° C for up to two times, each for 40 minutes, and then at 4100 min. -1 The solution was centrifuged at a speed of 100 °C for 1 hour.
[0134] According to the relative viscosity (η rel =η / η s ), the dimensionless SV value is determined as follows:
[0135] SV=(η rel -1)×1000
[0136] The proportion of particles in the film or polymer raw material is determined by ash determination and corrected by appropriate additional weighing. That is:
[0137] Weighing = (Weighing corresponding to 100% polymer) / [(100 - particle content weight %) / 100)].
[0138] Example
[0139] The following base materials were used to produce the membranes described below:
[0140] PET1 = polyethylene terephthalate made from ethylene glycol and terephthalic acid, SV value 820, DEG content 0.9 wt% (diethylene glycol content is monomeric).
[0141] PET2 = PCR raw material, produced from PET flakes obtained from so-called "PET post-consumer articles" (mainly bottles and trays made of PET) (e.g. available under the trade name MOPET (R), Morssinkhofk). Due to the condensation process, the SV values are higher than conventional PET, typically reaching values above 950, and the DEG content is about 1.5% by weight.
[0142] PET3 = polyethylene terephthalate composed of ethylene glycol and dimethyl terephthalate, SV value 820, DEG content of 0.9 wt% (diethylene glycol content is monomeric), 1.5 wt% of d 50 Silica pigment Sylobloc 46. Produced by PTA process. Catalyst is potassium titanium oxalate with 18 ppm titanium. Transesterification catalyst zinc acetate.
[0143] PET4 = polyethylene terephthalate with a SV value of 700, containing 20% by weight of Tinuvin 1577, UV stabilizer having the following composition: 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyl)oxyphenol (Ludwigshafen, Germany, BASF Tinuvin 1577 has a melting point of 149°C and is thermally stable at 330°C.
[0144] PET5 = polyethylene terephthalate, SV value 710, containing 25 mol% of isophthalic acid as comonomer.
[0145] Each layer of the above raw materials is melted in an extruder and extruded through a three-layer slit die (in the order of ABA / C layers) onto a cooled take-off roll. Then, the amorphous preformed film obtained in this way is first stretched longitudinally. The stretched film is corona treated in a corona discharger and then coated with the above solution by reverse engraving. The volume used is 6.6 cm 3 / m 2 The film is then dried at a temperature of 100°C and then cross-stretched, heat-set and rolled up. The conditions of the individual process steps are:
[0146] Longitudinal stretching: Temperature: 80℃ to 115℃
[0147] Longitudinal stretch ratio: 3.8
[0148] Transverse stretching: Temperature: 80℃ to 135℃
[0149] Transverse stretch ratio: 3.9
[0150] Annealing: at 25°C, 2 minutes
[0151] Embodiment 1:
[0152] Surface layers (A) and (C): Combine the following:
[0153] 10 wt% PET4
[0154] 7.2 wt% PET3
[0155] 82.8 wt% PET1
[0156] Base layer (B): Combine the following:
[0157] 90 wt% PET1
[0158] 10 wt% PET4
[0159] Coating applied only on top layer C (coated on one side):
[0160] Coating 1:
[0161] An anti-fog coating solution with the following composition was used:
[0162] 84.3 wt% deionized water
[0163] 5.82% by weight G-Polymer OKS 8089 (MCPP Europe GmbH)
[0164] 6.05% by weight Epocros WS700 (Nippon Shokubai Co., Ltd.)
[0165] 3.83% by weight Aerodisp W7622 (Evonik Resource Efficiency GmbH)
[0166] The different components were slowly added to deionized water while stirring for at least 30 minutes before use. The solid content was 15% by weight. The thickness of the dry coating was 80 nm.
[0167] Unless otherwise stated, coating was carried out in an in-line process. The properties of the films thus obtained are shown in Table 2.
[0168] Embodiment 2:
[0169] Compared to Example 1, the second top layer (A) was also coated with coating 1 as in Example 1. Coating on top layer (C): as in Example 1
[0170] Slowly add the components to deionized water while stirring for at least 30 minutes before use.
[0171] The solid content was 15% by weight. The thickness of the dry coating was 80 nm.
[0172] Embodiment 3:
[0173] In comparison to Example 1, PCR raw material (ie 90% PET2+10% PET4) was used to produce the base layer (B). In the resulting film, traces of minimal contaminants originating from the PCR raw material were visible.
[0174] Examples 4 and 5
[0175] The remaining examples were based on a similar production procedure as Inventive Example 1. The formulations of the base film and coating are described in Table 2 below:
[0176] Comparative Example 1
[0177] Paint 2:
[0178] A coating consisting of a hydrophilic coating, such as in EP 1 777 251 A1, wherein the dried product of the coating composition contains water, sulfopolyester, a surfactant and optionally an adhesion-promoting polymer. The film has a hydrophilic surface, which prevents the film from being atomized by water droplets within a short time. The following coating solution composition was used:
[0179] 1.0 wt% sulfopolyester (90 mol% isophthalic acid and 10 mol% copolyester of sodium sulfoisophthalate and ethylene glycol)
[0180] 1.0 wt% of an acrylic acid ester copolymer consisting of 60 wt% of methyl methacrylate, 35 wt% of ethyl acrylate and 5 wt% of N-hydroxymethyl acrylamide
[0181] 1.5% by weight of diethylhexylsulfosuccinic acid sodium salt (Lutensit A-BO BASF AG).
[0182]
[0183]
Claims
1. A greenhouse screen comprising strips (11) of film material, said strips (11) being interconnected by a yarn system of longitudinal threads (12, 14, 18) and transverse threads (13a, 13b; 15; 19) via a knitting, warp knitting or weaving process to form a continuous product, wherein at least 50% of said strips (11) comprise a single-layer or multi-layer polyester film having a transparency of at least 92%, wherein said polyester film has a first surface and a second surface, wherein a permanent anti-fog coating has been applied to at least one of said first surface or second surface of said polyester film, said anti-fog coating comprising: a) at least one water-soluble polymer; b) an inorganic hydrophilic material; and c) a cross-linking agent; The water-soluble polymer is a polyvinyl alcohol copolymer selected from ethylene glycol-polyvinyl alcohol copolymers or mixtures thereof.
2. The greenhouse screen according to claim 1, wherein the polyester film comprises a base layer (B) and a first cover layer (A), or a first cover layer (A) and a second cover layer (C), wherein: The first covering layer (A) is applied to the first side or the second side of the base layer (B), and the second covering layer (C), if present, is applied to the side of the base layer (B) opposite to the first covering layer (A).
3. Greenhouse screen according to claim 1 or 2, wherein the thickness of the polyester film is at least 10 μm and at most 40 μm.
4. Greenhouse screen according to claim 1 or 2, wherein the thickness of the polyester film is at least 14 μm and at most 23 μm.
5. Greenhouse screen according to claim 1 or 2, wherein the thickness of the polyester film is at least 14.5 μm and at most 20 μm.
6. The greenhouse screen according to claim 2, wherein the base layer (B) is at least 70% by weight of a thermoplastic polyester, based on the total weight of the base layer (B), wherein the thermoplastic polyester consists of at least 90% by mole of units derived from ethylene glycol and terephthalic acid or units derived from ethylene glycol and naphthalene-2,6-dicarboxylic acid.
7. Greenhouse screen according to claim 6, wherein the thermoplastic polyester consists of at least 95 mol% of units derived from ethylene glycol and terephthalic acid or from ethylene glycol and naphthalene-2,6-dicarboxylic acid.
8. Greenhouse screen according to claim 1 or 2, wherein the polyester film contains particles selected from the group consisting of calcium carbonate, amorphous silica, talc, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, lithium phosphate, calcium phosphate, magnesium phosphate, aluminum oxide, lithium fluoride, calcium, barium, zinc or manganese salts of used dicarboxylic acids, titanium dioxide, kaolin or particulate polymers consisting of crosslinked polystyrene and acrylate particles.
9. Greenhouse screen according to claim 2, wherein the base layer (B), and, if present, the first cover layer (A) and the second cover layer (C) comprise UV stabilizers.
10. Greenhouse screen according to claim 9, wherein the UV stabilizer is selected from the group consisting of triazines, benzotriazoles and benzoxazinones, wherein the base layer (B), the first cover layer (A) and, if present, the second cover layer (C) comprise UV stabilizers in an amount of 0.3% to 3% by weight, based on the weight of the respective layer. The greenhouse screen according to claim 10 , wherein the UV stabilizer is a triazine.
12. Greenhouse screen according to claim 10, wherein the second cover layer (C), if present, comprises a UV stabilizer in an amount of 0.75% to 2.8% by weight, based on the weight of the respective layer.
13. The greenhouse screen according to claim 1 or 2, wherein the anti-fog coating has a lower refractive index than the polyester film.
14. The greenhouse screen according to claim 1 or 2, wherein the ethylene glycol-polyvinyl alcohol copolymer is selected from propylene glycol-polyvinyl alcohol copolymer, butene glycol-polyvinyl alcohol copolymer, pentene glycol-polyvinyl alcohol copolymer or a mixture thereof.
15. The greenhouse screen according to claim 1 or 2, wherein the inorganic hydrophilic material is selected from inorganic alkoxides containing silicon, aluminum or titanium, kaolin, cross-linked polystyrene, acrylate particles, amorphous silica, fumed metal oxides and aluminum silicate.
16. The greenhouse screen according to claim 1 or 2, wherein the inorganic hydrophilic material is porous SiO2.
17. The greenhouse screen according to claim 1 or 2, wherein the inorganic hydrophilic material is SiO2 nanoparticles.
18. The greenhouse screen according to claim 1 or 2, wherein the inorganic hydrophilic material is fumed silica.
19. The greenhouse screen according to claim 1 or 2, wherein the inorganic hydrophilic material is hydrophilic fumed silica.
20. The greenhouse screen according to claim 1 or 2, wherein the crosslinking agent is an oxazoline based crosslinking agent.
21. Greenhouse screen according to claim 1 or 2, wherein the thickness of the anti-fog coating is at least 60 nm and at most 150 nm.
22. Greenhouse screen according to claim 1 or 2, wherein the thickness of the anti-fog coating is at least 70 nm and at most 130 nm.
23. Greenhouse screen according to claim 1 or 2, wherein the thickness of the anti-fog coating is at least 80 nm and at most 120 nm.
24. A greenhouse screen according to claim 1 or 2, wherein the anti-fog coating has been applied to the first surface or the second surface of the polyester film, and the surface of the polyester film opposite to the anti-fog coating has an anti-reflection modification, the anti-reflection modification: a) is an anti-reflective coating, or b) is the top layer modification.
25. Greenhouse screen according to claim 24, wherein said top layer modification has been formed by coextrusion on said base layer (B) and comprises a polyester having a lower refractive index than said polyester of said base layer (B).
26. The greenhouse screen of claim 24, wherein the anti-fog coating has a thickness of at least 30 nm when the anti-fog coating is located opposite the anti-reflective modification.
27. The greenhouse screen of claim 24, wherein the anti-fog coating has a thickness of at least 40 nm when the anti-fog coating is located opposite the anti-reflective modification.
28. The greenhouse screen according to claim 24, wherein when the anti-fog coating is located opposite the anti-reflective modification, the anti-fog coating has a thickness of at least 50 nm and at most 150 nm.
29. A greenhouse screen according to claim 1 or 2, wherein at least 60% of the strips in the screen shall be strips (11) of coated single or multi-layer polyester films.
30. Greenhouse screen according to claim 1 or 2, wherein at least 70% of the strips in the screen shall be strips (11) of coated single or multi-layer polyester films.
31. A greenhouse screen according to claim 1 or 2, wherein at least 80% of the strips in the screen shall be strips (11) of coated single or multi-layer polyester films.
32. A greenhouse screen according to claim 1 or 2, wherein at least 90% of the strips in the screen shall be strips (11) of coated single or multi-layer polyester films.
Citation Information
Patent Citations
anti-fog coating composition, anti-fog coating and anti-fog article
DE69833711D1
A green-house curtain
EP0109951A1
Polyester film with a cross-linked acrylic adhesion promoting layer
EP0144948A2
Silicone release coated polyester film
EP0769540A2
Polyolefin film compositions with permanent antifog properties
EP1152027A1